2000
DOI: 10.1086/308480
|View full text |Cite
|
Sign up to set email alerts
|

Collapse and Fragmentation Models of Tidally Interacting Molecular Cloud Cores. IV. Initial Slow Rotation and Magnetic Field Support

Abstract: Fragmentation has long been advocated as the primary mechanism for explaining the observed binary frequency among preÈmain-sequence stars and, more recently, for explaining the emerging evidence for binary and multiple protostellar systems. The role of magnetic Ðelds and ambipolar di †usion is essential to understand how dense cloud cores begin dynamic collapse and eventually fragment into protostars. Here we consider new numerical models of the gravitational collapse and fragmentation of slowly rotating molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Thus, in a more complete theoretical calculation, magnetic fields must be taken into account. As shown by Sigalotti & Klapp (2005), it is expected that one of the main effects of magnetic fields would be to slow down the collapse of the dense core.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Thus, in a more complete theoretical calculation, magnetic fields must be taken into account. As shown by Sigalotti & Klapp (2005), it is expected that one of the main effects of magnetic fields would be to slow down the collapse of the dense core.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In the protostellar context, such strong fields may also be relevant for the problem of binary formation (cf. Sigalotti & Klapp 2000).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(83)-(89) have only been performed in axisymmetry. However, some 3D fragmentation simulations [309][310][311] have begun to appear recently, which include the effects of magnetic support and ambipolar diffusion in an approximate fashion. In these calculations, the starting point of the evolution is provided by a magnetically stable (subcritical) condensation that results from adding a magnetic field pressure, B 2 /8π, to a reference state consisting of a thermally supercritical, rigidly rotating, Gaussian cloud core of prolate shape and central density ρ 0 .…”
Section: Fragmentation Models With Magnetic Fieldsmentioning
confidence: 99%
“…These models were subsequently extended to include the collapse of slowly rotating clouds by Boss 310 and Sigalotti and Klapp. 311 Boss 310 performed a set of calculations with either solid-body or differential rotation and varied β(1.2 × 10 −4 ≤ β ≤ 0.012). He found that such clouds can fragment into a binary protostar, provided that β > 0.01.…”
Section: Fragmentation Models With Magnetic Fieldsmentioning
confidence: 99%